2014
DOI: 10.1515/gej-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization and Productivity Performance: Evidence from the Australian Passenger Motor Vehicle Industry

Abstract: This paper contributes to the ongoing debate about the effects of trade liberalization on productivity performance of the Australian passenger motor vehicle industry, which has experienced significant liberalization over the years. Our analysis indicates that trade liberalization had a negative impact on productivity growth, at least in the immediate post-liberalization period. Empirical results suggest that economies of scale and tariff protection improve productivity, while industry assistance (such as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In summary, our results suggest that protection and IA reduce IP in the Australian PMV industry. These findings together bring home an important message that lowering NRP and IA, by increasing import competition, may help improve the productivity performance of the Australian PMV industry (Bopage, 2010).…”
Section: Results Of the Determinants Of Import Penetrationmentioning
confidence: 71%
See 1 more Smart Citation
“…In summary, our results suggest that protection and IA reduce IP in the Australian PMV industry. These findings together bring home an important message that lowering NRP and IA, by increasing import competition, may help improve the productivity performance of the Australian PMV industry (Bopage, 2010).…”
Section: Results Of the Determinants Of Import Penetrationmentioning
confidence: 71%
“…Information concerning the use of dummy variables for export incentives, government assistance and foreign investment was obtained from government files and record, interviews with automotive executives, Lloyd (2008) and Bopage (2010).…”
mentioning
confidence: 99%
“…Studies on the effects of liberalization on the AAI are extremely limited and the available studies largely focus on trade structure. Only a few studies that have examined the effects of globalization on the AAI have concluded that trade restrictions thwart the growth of industry, prevent economies of scale due to the small size of domestic market and contribute to inefficiency (Bopage, 2010). In an attempt to examine the effects of policy liberalization on the AAI, the Industry Commission (IC, 1997) examined (i) factors affecting the automotive industry in Australia; (ii) how a reduction in assistance has created a more competitive environment and (iii) how the industry would evolve through the following decades within an environment of trade liberalization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2.See, Bopage (2010) and literature cited therein for studies examining trade performance of the AAI.…”
mentioning
confidence: 99%